Arsenic, internal cancers, and issues in inference from studies of low-level exposures in human populations - Cantor, Kenneth P.; Lubin, Jay H. (Toxicology and applied pharmacology, 2007)
Epidemiologic data from regions of the world with very high levels of arsenic in drinking water (> 150 μg/L) show a strong association between arsenic exposure and risk of several internal cancers. A causal interpretation of the data is warranted based on the strength and consistency of study findings. At lower levels of exposure (< 100 μg/L), in the absence of unambiguous human data, extrapolation from the high-exposure studies has been used to estimate risk. Misclassification of exposure usually results in depressing observed levels of risk, and studies conducted in populations with exposures below 100 μg/L have been limited by the challenge of estimating past exposures, a critically important aspect of studying relative small increases in risk. Relatively small study size contributes to the variability of findings in most studies and makes interpretation of results all the more challenging. The effects on risk estimates of exposure misclassification and small study size under various scenarios are graphically illustrated. Efforts are underway to improve exposure assessment in a large case–control study of bladder cancer in a region of the United States with moderately elevated levels of arsenic in drinking water.